USE OF AGRICULTURAL HABITATS AND FOODS BY WILD TURKEYS IN SOUTHWESTERN WISCONSIN - R. Neal Paisley; Robert G. Wright; John F. Kubisiak (Wildlife Society Bulletin)
Abstract: As eastern wild turkey (Meleagris gallopavo silvestris) densities increased in southwestern Wisconsin during the 1980s, the perception that turkeys were causing significant agricultural crop damage began to develop among rural landowners. To address this issue, we investigated the use of agricultural habitats and foods by wild turkeys during the 1988‐93 growing seasons. Habitat use was estimated for radio‐tagged hens during summer (n = 41) and fall (n = 18) to determine the importance of crop fields. Food habits were determined from wild turkeys collected in crop fields (primarily corn, alfalfa, and oats) by research personnel during spring (n = 100) and summer (n = 45; entire sample from brood flocks) and from legally harvested birds during fall (n = 250). During summer, hens with broods (n = 16) used crop fields more (34.6 vs. 20.5%) and woodlands less (54.8 vs. 64.0%) than hens without broods (n = 25) (P < 0.05). Overall, hens used crop fields more (27.5 vs. 17.3%) and woodlands less (59.4 vs. 68.3%) during summer than during fall (P < 0.05). Agricultural foods constituted 52% of the diet during the growing season. Corn, nearly all waste, made up 77% of all agricultural foods consumed and was the primary food selected during spring and fall. Invertebrates, principally grasshoppers (Locustidae), were the most important food of brood flocks during summer and constituted 68% of the diet. Although agricultural habitats were important to wild turkeys during the growing season, the consumption of harvestable agricultural crops was low.